Comunicação e aprendizagem: utilização de tecnologia móvel aplicada na educação presencial e EAD - Barros, Lorena Simone Nascimento (2016)
The research understands the dialogue as the main notion in the communication and learning definitions: it is impossible to have communication without dialogue and, therefore, learning without communication. Thenceforth, with historical and empirical support in distance learning and online teaching, we investigated the use of mobile devices in education. Our empirical and exploratory research - qualitative - had as methodological approach a study of multiple cases, carried out with the objective of analyzing the devices mobility in internet spaces , applied to undergraduate courses of Pedagogy and Languages (both in distance education) and Communication in Digital Media (formal learning), of Universidade Federal da Paraíba (UFPB). This investigation took into account the researcher's participant observations, as a student and an English teacher, in order to understand the use of mobile technologies in the learning process. The analysis allowed the understanding of the changes that the connected mobility have brought to the notions of time and space and thereby the reconfigurations on the way we learn. In this sense, participation, collaboration and interaction are seen as essential conditions for learning in mobility times.